2000
DOI: 10.1292/jvms.62.465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linoleic Acid-Albumin on Post-Thaw Survival of in vitro-Produced Bovine Embryos at the 16-Cell Stage.

Abstract: ABSTRACT. The effect of addition of linoleic acid-albumin (LAA) to culture medium before freezing on the survival rate of bovine 16-cell embryos after freezing-thawing was investigated. Embryos were incubated in CR1aa containing LAA (0.25 mg/ml) for 4 days after insemination. A conventional slow cooling method was used, in which embryos were cooled at a rate of 0.3°C/min to 30°C in medium supplemented with 1.5 M ethylene glycol and 0.2 M trehalose. The developmental rate to the blastocyst stage of thawed embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…However, blastocyst development and quality of 16-cell stage embryos frozen even in ethylene glycol was still inferior to those of fresh embryos (67.3%, 37/55). When the 16-cell stage embryos were produced in CR1aa [14] containing 0.25 mg/mL LAA for 4 days after IVF, the postthaw survival of 16-cell stage embryos produced in LAA-containing medium was higher than that of those cultured without LAA [15].…”
Section: Ethylene Glycol As a Permeable Cryoprotectant For Freezing Omentioning
confidence: 90%
“…However, blastocyst development and quality of 16-cell stage embryos frozen even in ethylene glycol was still inferior to those of fresh embryos (67.3%, 37/55). When the 16-cell stage embryos were produced in CR1aa [14] containing 0.25 mg/mL LAA for 4 days after IVF, the postthaw survival of 16-cell stage embryos produced in LAA-containing medium was higher than that of those cultured without LAA [15].…”
Section: Ethylene Glycol As a Permeable Cryoprotectant For Freezing Omentioning
confidence: 90%
“…(2006) found no difference in blastocyst production for cultures supplemented with amino acids and oestrous cow serum and/or bovine serum albumin (BSA), but post‐thaw survival rates were higher for medium containing amino acids and BSA (51.9% vs. 25%). Moreover, bovine embryos cultured in CR1aa without serum prior to vitrification had better survival post‐warming (Tominaga et al. 2000; Mucci et al.…”
Section: Cryotolerancementioning
confidence: 99%
“…It is naturally found to be accumulated in the body fluids of many organisms as winter advances (23). Several workers have used this compound for effective cryopreservation of various tissues and cells like sperms (24), embryos (25), islets (26), RBCs (27), and other biological samples (28). Kapicht et al (29) reported freezing of human bone marrow and PBSCs with trehalose at vitrification concentrations without DMSO.…”
Section: Figmentioning
confidence: 99%